A public–private partnership model to reduce tuberculosis burden in Akwa Ibom State – Nigeria. (March 2015) - Asuquo, A.E.; Pokam, B.T.; Adindu, A.; Ibeneme, E.O.; Ekpereonne, E.; Obot, V.
Abstract: Background: Tuberculosis (TB) infection and spread are preventable, and TB disease is curable depending on the individual and community knowledge of causes of the disease, mode of prevention and cure. Objective: Following a previous program carried out in 2006 in Akwa Ibom State (AKS) of Nigeria that focussed on creating awareness about TB and educating the communities on appropriate care-seeking attitudes, an intervention to reduce the burden of the disease in 18 communities of the State was carried out over a period of one year (2010–2011). The program was phased and was comprised of three components: educational intervention, TB case detection and integration into the State National Tuberculosis and Leprosy Control Programme (NTBLCP), as well as laboratory capacity building. Methods: Standard pretested questionnaires were administered to community residents to test their knowledge, attitudes and practices concerning TB. Information about causes, symptoms and prevention of TB was disseminated in community town halls, churches, markets and schools. Individuals who were coughing for three weeks or more were investigated for TB following clinical examination by a physician. Three sputum samples (spot-morning-spot) were obtained from each individual and examined microscopically for the presence of acid-fast bacilli (AFB) using the Ziehl-Neelsen staining technique. Those with positive AFB results were integrated into the existing NTBLCP TB treatment facilities for immediate commencement of Directly-Observed Therapy Short Course (DOTs). Treatment outcome was monitored by retesting patients' sputum after 2, 5 and 7 months. Two new laboratories were facilitated while existing laboratory capacity was built by providing higher resolution microscopes, power-generating plants, refrigerators and locally-fabricated incinerators. The program was facilitated by a public–private partnership. Effective Health Care Alliance Research Programme (Nigeria), in collaboration with Nigeria National Petroleum Cooperation and Mobil Producing Nigeria Unlimited (NNPC/MPN) Joint Venture, utilized health personnel from the Akwa Ibom State NTBLCP who conducted laboratory testing and supervised the treatment. Results: The 916 responses to the questionnaires showed that 549/841 (65%) correctly identified that TB is airborne, and 759/871 (86%) were aware that TB could be cured by anti-TB medication. Responses to care-seeking attitudes were provided by 123 respondents. Of this number, fear of stigmatization was the reason for 31% (38) seeking care in unorthodox facilities, while 43% (53) did not believe that orthodox medicine could cure their symptoms. Of the 374 detected cases, 9 did not commence treatment. Hence, 365 cases were placed on DOTs; 36 defaulted while 11 died or failed to convert after the seventh month. At the end of month 8, cure was achieved for 318 (87.1%) of the cases. Conclusion: Though the previous intervention might have helped to increase the knowledge of the respondents about TB in the community and helped to improve their care-seeking attitudes, sustaining active case finding through Public–Private Partnership can go a long way to reduce TB burden, especially in rural communities where health care systems are generally weak or inadequate.